A Comparative Study of the Metabolic and Skeletal Response of C57BL/6J and C57BL/6N Mice in a Diet-Induced Model of Type 2 Diabetes. (3rd June 2015) - Rendina-Ruedy, Elizabeth; Hembree, Kelsey D.; Sasaki, Angela; Davis, McKale R.; Lightfoot, Stan A.; Clarke, Stephen L.; Lucas, Edralin A.; Smith, Brenda J.
Abstract : Type 2 diabetes mellitus (T2DM) represents a complex clinical scenario of altered energy metabolism and increased fracture incidence. The C57BL/6 mouse model of diet-induced obesity has been used to study the mechanisms by which altered glucose homeostasis affects bone mass and quality, but genetic variations in substrains of C57BL/6 may have confounded data interpretation. This study investigated the long-term metabolic and skeletal consequences of two commonly used C57BL/6 substrains to a high fat (HF) diet. Male C57BL/6J, C57BL/6N, and the negative control strain, C3H/HeJ, mice were fed a control or HF diet for 24 wks. C57BL/6N mice on a HF diet demonstrated an increase in plasma insulin and blood glucose as early as 4 wk, whereas these responses were delayed in the C57BL/6J mice. The C57BL/6N mice exhibited more severe hepatic steatosis and inflammation. Only the C57BL/6N mice lost significant trabecular bone in response to the high fat diet. The C3H/HeJ mice were protected from bone loss. The data show that C57BL/6J and C57BL/6N mice differ in their metabolic and skeletal response when fed a HF diet. These substrain differences should be considered when designing experiments and are likely to have implications on data interpretation and reproducibility.